Operant conditioning of autobiographical memory retrieval - Debeer, E; Raes, F; Williams, J; Craeynest, M; Hermans, D (2014)
Functional avoidance is considered as one of the key mechanisms underlying overgeneral autobiographical memory (OGM). According to this view OGM is regarded as a learned cognitive avoidance strategy, based on principles of operant conditioning; i.e., individuals learn to avoid the emotionally painful consequences associated with the retrieval of specific negative memories. The aim of the present study was to test one of the basic assumptions of the functional avoidance account, namely that autobiographical memory retrieval can be brought under operant control. Here 41 students were instructed to retrieve personal memories in response to 60 emotional cue words. Depending on the condition, they were punished with an aversive sound for the retrieval of specific or nonspecific memories in an operant conditioning procedure. Analyzes showed that the course of memory specificity significantly differed between conditions. After the procedure participants punished for nonspecific memories retrieved significantly more specific memories compared to participants punished for specific memories. However, whereas memory specificity significantly increased in participants punished for specific memories, it did not significantly decrease in participants punished for nonspecific memories. Thus, while our findings indicate that autobiographical memory retrieval can be brought under operant control, they do not support a functional avoidance view on OGM. © 2013 © 2013 Taylor and Francis.